Inverted‐V Electron Acceleration Events Concurring With Localized Auroral Observations at Mars by MAVEN. Issue 9 (25th April 2020) - Xu, Shaosui; Mitchell, David L.; McFadden, James P.; Fillingim, Matthew O.; Andersson, Laila; Brain, David A.; Weber, Tristan; Schneider, Nicholas M.; Jain, Sonal; Fowler, Christopher M.; Lillis, Robert; Mazelle, Christian; et al.
Abstract: From February to March 2019, the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft repeatedly observed aurora near periapsis over Mars' southern strong crustal fields. During these orbits, the Solar Wind Electron Analyzer observed accelerated electrons at similar locations to where the auroras were observed, resembling the inverted‐V structure observed near Earth's auroral region. In this study, we present a case study of such an acceleration event, where we estimate a field‐aligned electrostatic potential drop of ∼440 V. We determine the field‐aligned current from the observed magnetic perturbation reaches 1.1 μA/m 2, agreeing reasonably well with the estimated net electron current carried by acceleration electrons with a maximum of 2.5 μA/m 2 . Similar to Earth, the potential drop develops when the ambient plasma cannot sustain the imposed field‐aligned current. We also estimate the potential layer to be located above 750‐ to 850‐km altitude and the associated electric field to be ∼0.6 V/m. Key Points: We estimate a field‐aligned potential drop of 440 V during an inverted‐V electron acceleration event concurring with auroral observations The current density estimated from the observed magnetic perturbation reaches 1.1 μA/m2, agreeing with estimated net electron current Similar to Earth, this potential drop develops when the ambient plasma is unable to support the necessary field‐aligned current